Efektivitas Penggunaan Media Pembelajaran Flashcard dalam Keterampilan Menulis Aksara Sunda Siswa Madrasah Ibtidaiyah - Suci Zakiyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2022)
The ability to write Sundanese script has received serious attention because it is related to the preservation of intangible cultural heritage, many of the MI level students who cannot write Sundanese script do not even know what Sundanese script is like. Implementation of learning to write Sundanese script in MI can be carried out using flashcard learning media. The formulation of the problem in this study in general is